Cu3BiS3 Nanocrystals as Efficient Nanoplatforms for CT Imaging Guided Photothermal Therapy of Arterial Inflammation - Lu, Ran; Zhu, Jingyi; Yu, Chaowen; Nie, Zhonglin; Gao, Yong (Frontiers in Bioengineering and Biotechnology, 2020)
Cardio-cerebrovascular diseases caused by chronic inflammatory atherosclerosis seriously damage human health. Nano-photothermal technology has been proven to inhibit the development of vascular inflammation, but the currently reported photothermal agents cannot efficient monitor it during the development of the disease. Herein, we designed and prepared an efficient bifunctional nanoplatform for CT imaging guided photothermal therapy of arterial inflammation. Cu3BiS3 nanocrystals with a size of about 12 nm were synthesized by a simple hydrothermal method. The as-prepared Cu3BiS3 nanocrystals showed intense absorption in the NIR region, thus exhibited amazing photothermal effect. The photothermal conversion efficiency of Cu3BiS3 nanocrystals was reach up to 58.6% under the excitation of an 808 nm laser with a power density of 0.4 W cm–2. Cu3BiS3 nanocrystals can efficiently kill the macrophages both in vitro and in vivo, which plays an important role in the development of atherosclerosis, thus can be used as an effective way to inhibit the occurrence of hypertension. Importantly, Cu3BiS3 nanocrystals can be used as an efficient CT contrast agent to monitor carotid inflammation. Our work provides an insight for imaging guided photothermal therapy of arterial inflammation.